Effect of endometriosis on prognosis of ovarian clear cell carcinoma: a 10-year retrospective study - He, Yang; Cao, Bo (Frontiers in Oncology, 2024)
IntroductionEndometriosis is considered as a precancerous lesion for OCCC; however its prognostic significance remains controversial. This study aims to evaluate the prognostic significance of endometriosis in patients with ovarian clear cell carcinoma (OCCC) and analyze the impact of other clinical pathological features on prognosis. Additionally, we also assess the role of laparoscopic surgery and chemotherapy in OCCC, hoping to provide evidence for improving the clinical diagnosis and treatment of OCCC.MethodsA retrospective analysis was conducted on medical records of 105 OCCC patients diagnosed and treated at the Gynecologic Cancer Center of Hubei Cancer Hospital in China from 2013 to 2022. Based on the presence or absence of endometriosis, OCCC patients were divided into two groups: a group with ovarian endometriosis consisting of 44 cases (41.9%) (EC-positive group) and a group without ovarian endometriosis consisting of 61 cases (58.1%)(EC-negative group). Clinical pathological characteristics, progression-free survival (PFS), and overall survival (OS) were compared between the two groups.ResultsThere were no statistically significant differences between the two groups in terms of age, CA125, tumor size, FIGO stage, adjuvant chemotherapy regimen, or chemotherapy efficacy (P>0.05). Residual tumor after surgery, staging, site invasion involvement, presence of ascites, positive cytology in ascitic fluid, lymph node metastasis, and chemotherapy efficacy were predictive factors for recurrence among patients with statistical significance (P<0.10); chemotherapy efficacy remained as independent predictors for recurrence (P<0.05); staging and chemotherapy efficacy remained as independent predictors for survival (P<0.05). There was no statistically significant difference observed between both groups regarding OS or PFS.ConclusionIn this study, co-existing endometriosis was not a prognostic factor for survival in patients with OCCC. The most important predictors of OS and PFS were FIGO stage and chemotherapy sensitivity. The intrinsic link between endometriosis and OCCC requires larger, better-designed prospective studies to draw more definitive conclusions.